Recovering PHA from mixed microbial biomass: Using non-ionic surfactants as a pretreatment step - Colombo, Bianca (2020)
Polyhydroxyalkanoates (PHA) are biodegradable plastics of microbial origin, whose biodegradability and thermochemical properties make them greener alternatives to conventional plastics. Despite their high industrial potential, the PHA’ high production costs still hinder their application. Mixed microbial biomass combined with agro-industrial wastes are being used to strategically reduce these costs. However, it is still necessary to optimize the downstream processing, where the extraction process amounts to 30–50% of the total costs. Conventional processes apply chlorinated solvents to recover PHA from microbial biomass but cannot be implemented industrially due to environmental regulations. Alternative solvents, with good results of purity and recovery yields, usually have a negative impact on the molecular weight of the final polymer. In this work, the addition of a pre-treatment based on non-ionic surfactants (Tween® 20, Brij® L4, and Triton™ X-114) to extract PHA from mixed microbial biomass selected on fermented agro-industrial wastes was investigated. The best results were obtained with Tween® 20 allowing for an increase in 50% compared with the use of dimethylcarbonate without any pre-treatment (from 38.4 ± 0.8% to 53 ± 2%) and very close to those obtained with chloroform (63%). The extracted polymer was analysed and characterized, revealing a PHA of high purity (>90%) and low molecular weight loss (under 24%). Additionally, a material-focused economic and a carbon footprint analysis were performed and supported the selection of the method as one of the cheapest options and with the lowest carbon footprint.